A Systematic Literature Review of the Feasibility of a Translanguaging Pedagogy in the Foundation Phase - Carrim, Ameera; Nkomo, Sibhekinkosi Anna (Universitas Pendidikan Mandalika, 2023)
Many South African educational contexts, including the Foundation Phase are linguistically diverse. However, this diversity is not mostly catered for as evidenced by the prevalent monoglossic ideologies. This has resulted in low literacy levels in South Africa, which indicate a poor literacy foundation and limit learners’ ability to learn effectively and excel academically. Over the past decade, a number of literacy intervention programmes have been implemented at national and provincial level, but the impact has been minimal. There is need to explore and adopt other approaches to literacy development such as the translanguaging pedagogy which has been reported to be successful in other phases of education. However, there has not yet been studies that report on translanguaging undertaken at Foundation Phase in South Africa. Thus, this study explored the feasibility of a translanguaging pedagogy in the Foundation Phase to develop literacy for multilingual English first additional language learners. Through a systematic review, translanguaging studies conducted between the years 2015-2022 in South Africa and internationally were reviewed and analysed using a thematic analysis approach. Finding from this study reveal that learners’ home language should be considered as a resource for attaining deeper levels of meaning. By adopting a translanguaging approach, teachers can enhance multilingual learners’ literacy skills through strategies such as home-languaging, translation, juxtaposing languages and the flexible and dynamic use of the multimodal semiotic repertoire. However, future research is recommended to investigate the application of this pedagogy in the Foundation Phase classrooms in South Africa.